2023
DOI: 10.1111/cjag.12329
|View full text |Cite
|
Sign up to set email alerts
|

Access to credit and heterogeneous effects on agricultural technology adoption: Evidence from large rural surveys in Ethiopia

Abstract: Modern agricultural technologies hold huge potential for increasing productivity and reducing poverty in developing countries. However, adoption levels of these technologies have remained disappointingly low in Africa. This paper analyzes the effect of access to credit on the likelihood of adoption and use intensity of chemical fertilizers using data from large rural surveys in Ethiopia. Using a heteroscedasticity-based identification strategy to address the endogenous nature of access to credit, we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For example [ 33 ], reported that majority of farmers in Nigeria and other Sub-Saharan African countries often finance modern input purchases with cash from non-farm activities and crop sales. On the other hand, credits are often taken to complement household food availability, and credit cost servicing (transaction costs, interest and repayments) might crowd out available resources to finance the technologies and discourage investments in improved technologies [ 34 , 35 ].…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…For example [ 33 ], reported that majority of farmers in Nigeria and other Sub-Saharan African countries often finance modern input purchases with cash from non-farm activities and crop sales. On the other hand, credits are often taken to complement household food availability, and credit cost servicing (transaction costs, interest and repayments) might crowd out available resources to finance the technologies and discourage investments in improved technologies [ 34 , 35 ].…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Subsistence production systems are dominated by staple crop production, and cash inflows do not arrive when inputs are needed to be purchased due to high seasonality of economic activities (Christiaensen, 2017). As a result, these households face binding liquidity constraints to finance improved varieties (Regassa et al, 2023). On the other hand, market-oriented groundnut farmers may have relatively better capacity to adopt improved varieties.…”
Section: Latent Class Analysesmentioning
confidence: 99%
“…However, despite demonstrated productivity gains, adoption rates of improved varieties of many crops remain disappointingly low (Miriti et al, 2023). The literature has put forward several complementary explanations, including missing markets for risk and credit (Karlan et al, 2014;Regassa et al, 2023), limited information and social networks (Shikuku and Melesse, 2020), and behavioral constraints (Duflo et al, 2011). An alternative explanation could be that improved varieties do not possess traits that farmers value most.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, credit constraints could hamper optimal resource allocation for food manufacturing firms and deter productivity-enhancing investments. The effects of credit on technology adoption are larger for creditconstrained producers compared with credit nonusers (Regassa et al, 2023). Countries should also improve the quality of financial institutions because better access to financing could utilize the productivity-enhancing effect of leverage, as seen in Figure 1.…”
Section: Nakatani | 207mentioning
confidence: 99%